If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(h + 3) = 2(6m + 8) Reorder the terms: 7(3 + h) = 2(6m + 8) (3 * 7 + h * 7) = 2(6m + 8) (21 + 7h) = 2(6m + 8) Reorder the terms: 21 + 7h = 2(8 + 6m) 21 + 7h = (8 * 2 + 6m * 2) 21 + 7h = (16 + 12m) Solving 21 + 7h = 16 + 12m Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 7h = 16 + -21 + 12m Combine like terms: 21 + -21 = 0 0 + 7h = 16 + -21 + 12m 7h = 16 + -21 + 12m Combine like terms: 16 + -21 = -5 7h = -5 + 12m Divide each side by '7'. h = -0.7142857143 + 1.714285714m Simplifying h = -0.7142857143 + 1.714285714m
| 1/4x-2/3y=8 | | 10x-(9x-6)=10 | | 1/9*9w | | 3(4z+2)-7=95 | | 4x+3/12+x-3/2=3x+1/4 | | 3/4(2x-6)=1/2x-4 | | 3(5h-12)=9 | | 0=3x^2+4 | | 0=3x^2-900 | | 52=28-3(x-4) | | a-2b=8 | | 12.95x=388.5 | | 2(8-d)=3d+4-d | | 11x+12-8x=-3 | | 2(3x-7)=2x+2 | | 152=25x | | 4(a-6)-3(4a+4)=-4a | | -7y-4=-5y+4 | | -3x+18+9x=-3x+5x+2x | | 7e^3x=21e^7x | | 3x+2(x+7)-5=4(x+3)-3(x-1) | | 6(t-4)+6t=(2t+3)-9 | | 35/7-21/5 | | 3-3-3-2-32+422= | | -6+2z-4z=30 | | 3z/8-z/10=6 | | 2(11-6x)-3(7-4x)=1 | | x/3+6=3x-12+x/3 | | 15x+17x+2x=14+2 | | 5x+4(3x-10)=2(x-4) | | 16+9(12/3*2)-7 | | 4(7s-3)-8(s+2)= |